Effects of poly(vinyl alcohol) and poly(acrylic acid) on interfacial properties and stability of compound droplets. (24th January 2020) - Liu, Meifang; Zheng, Yueqing; Liu, Yiyang; Zhang, Zhanwen; Wang, Yuguang; Li, Jing; Chen, Qiang; Li, Jie; Huang, Yawen; Yin, Qiang
Abstract: Polymer shells, as the container of deuterium and tritium fuels, are indispensable parts for preparing the target in the inertial fusion experiments and the future inertial fusion energy plants. It is important to ensure the stability of the corresponding compound droplets, the precursor of these polymer shells. The selection of surfactants is crucial in the preparation of the compound droplets due to their important role on the stability of the compound droplets. In this paper, the effects of the concentrations of the poly (vinyl alcohol) (PVA) and the poly (acrylic acid) (PAA), and their molecular weights on the bulk and interfacial properties, as well as the relationship between the properties and the stability of the compound droplets were investigated. Moreover, the mechanisms of the PVA and the PAA preventing the coalescence and the rupture of the compound droplets were also discussed. Lower interfacial tension and higher bulk viscosity benefited reducing the risk of the rupture and the coalescence. The interfacial dilational viscoelasticity (elastic modulus, viscous modulus and phase angle) also showed an important influence on the rupture and the coalescence. This work provides a more comprehensive understanding of the coalescence and the rupture, and gives some practical advices on selecting optimal concentration of the surfactant and its molecular weight, benefiting the preparation of stable compound droplets. Highlights: Stable compound droplets for ICF polymer shells were successfully prepared by using the surfactants (PVA and PAA). Effects of the surfactants (PVA and PAA) concentration and their molecular weights on interfacial properties was revealed. Mechanism of the surfactants (PVA and PAA) preventing the coalescence and rupture of compound droplets was proposed. Forced-contact experiment was designed to predict the coalescence possibility.